1997
DOI: 10.1055/s-0038-1665430
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Events during Oral Anticoagulant Treatment: Results of the Inception-cohort, Prospective, Collaborative ISCOAT Study

Abstract: SummaryThe paper reports on rate and type of thrombotic events occurring during the observational, prospective, inception-cohort, multicenter ISCOAT study. 2,745 unselected, daily practice patients, consecutively referring to 34 Italian anticoagulation clinics to monitor the oral anticoagulant treatment, were included in the study from beginning of their first anticoagulant course. During a total follow-up of 2,011 patient-years of treatment 70 thrombotic events (3.5 per 100 patient years) were recorded in 67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 0 publications
2
89
0
1
Order By: Relevance
“…[24][25][26][27][28][29] For our base analysis, we grouped the person-years of observation and events from these studies in the ratio category of 3-5. We repeated our analysis after imputing the person-years of observation and the number of events that occurred when the ratio exceeded 5.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…[24][25][26][27][28][29] For our base analysis, we grouped the person-years of observation and events from these studies in the ratio category of 3-5. We repeated our analysis after imputing the person-years of observation and the number of events that occurred when the ratio exceeded 5.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…We included 19 studies published between 1992 and 2007 in our analysis 6,[21][22][23][24][25][26][27][28][29][32][33][34][35][36][37][38][39][40] (Table 1). Of these, 14 reported both hemorrhagic and thromboembolic events, 6,21,23,25,[27][28][29][32][33][34][35][36][37]39 3 reported only hemorrhagic events, 22,38,40 and 2 reported only thromboembolic events.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PROLONG study, patients with an abnormal D-dimer level 1 month after discontinuation of anticoagulant for treatment of unprovoked VTE were randomized to resume warfarin or not. When the primary end-points of recurrent VTE and major bleeding were assessed, there were three events among the 103 [133,134]. Poor-quality INR control, as assessed by the percentage of time with INR <1.5, is associated with a long-term higher risk of recurrent VTE after eventual anticoagulant cessation (RR, 2.7; 95% CI, 1.39-5.25; P=0.003) [135].…”
Section: Recommendationsmentioning
confidence: 99%
“…In the ISCOAT study, the most large, prospective Italian investigation study, including a cohort from 34 ACs, the incidence of major bleeding complications was 1.25 for 100 patient-years, whereas the incidence of thromboembolic events was 3.5 for 100 patient-years (Palareti el al., 1997). Literature analysis showed that patients on RMC had a 2-fold increase (2.5 vs 1.25% patient-years) and 3-fold increase (10.5 vs 3.5% patient-years) of bleeding and thromboembolic risks, respectively, compared to patients followed by AC (Palareti et al, 1996;Palareti et al, 1997) (Tab. 1).…”
Section: Cost Analysis Of Different Management Strategiesmentioning
confidence: 99%